Rhinoplasty by relocation of autografts in patients with nasal deformities. Cienfuegos, 2009-2019 - Bernaldo Canto Vidal; Beatriz María Borrel Fuster; Emma Gil Ojeda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: In modern rhinoplasty there are new concepts aimed at achieving the ideal model of a nose. Many techniques have become old, but new, less invasive ones have emerged. Objective: to describe the results of rhinoplasty using the autograft relocation technique in patients with nasal deformities. Methods: a descriptive case series study conducted at the Dr. Gustavo Aldereguía Lima General University Hospital, in Cienfuegos. 25 patients were included in the research, who attended the Maxillofacial Surgery consultation due to nasal deformities, between 2009 and 2019, to whom the rhinoplasty surgical technique (the modified Joseph technique) was applied. Age, sex, skin color, type of graft, technique used (endonasal, open) and type of anesthesia were analyzed. Results: female sex and white skin color predominated. The most used surgical technique was endonasal (20 patients). All were operated under local anesthesia. The largest age group was 15-30 years old. The osteocartilaginous hump was the graft used in 72% of the cases. Conclusion: with the autograft relocation technique, favorable results were obtained in the case series described. This is one of the most advanced in the context of nasal cosmetic surgery.